40Ar/39Ar age of Mendanha Alkaline Intrusion, Rio de Janeiro, Brazil - Mota, C.; Geraldes, M.; Jourdan, Fred (Laboratorio Nacional de Energia e Geologia, 2014)
The Mendanha Alkaline Intrusion is one of many alkaline occurences of the Southeastern Brazil Alkaline Province. It comprises plutonic rocks (alkali-syenites and syenites) and hypabyssal types (trachytes and ignibrites). In this work is presented new 40 Ar/ 39 Ar ages for this massif. The last reported ages were about 74 My and 65 My by K/Ar method published in 1988. The obtained results show ages of about 64 My (64.12 ± 0.40, 64.04 ± 0.42) e 58 My (58.55 ± 0.45, 57.95 ± 0.69), which are correlated to neighbour magmatic intrusions.